{Disordered eating attitudes and emotional/behavioral adjustment in Greek adolescents} - Bacopoulou, F.; Foskolos, E.; Stefanaki, C.; Tsitsami, E.; Vousoura, E. (Eating and Weight Disorders, 2017)
{© 2017 Springer International Publishing AG, part of Springer Nature Purpose: The aim of this study was to examine the relationship between disordered eating attitudes and emotional/behavioral adjustment in Greek adolescents as well as the moderating role of gender and body mass index (BMI) in this relationship. Methods: Ninety adolescents, 11–18 years old, were assessed using anthropometric measurements; demographics, eating attitudes and level of emotional/behavioral adjustment were examined via self-reported questionnaires. Results: Disordered eating attitudes were prevalent in 17.8% of the sample. A significant relationship was found between disordered eating attitudes and Youth Self-Report (YSR) anxiety score (r = .22, p < .05). Gender significantly moderated the relationship between YSR anxiety symptoms and Eating Attitudes Test (EAT) scores (b = .59
Keywords: adolescence; anxiety; Bulimia; Dieting; Disordered eating